PROBLEMS RELATED TO MARKETING RESEARCH IN FURNITURE MANUFACTURING ENTERPRISES - Musayeva Shoira Azimovna, (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article examines whether the furniture fully meets his needs, selling the goods from the market, company store or online, what are the advantages of the goods, what kind of guarantee the seller gives and how long the goods can be used